(untitled) (Medico Legal Update, 2021)
Background: Obesity is a grave public health threat, more serious even than the opioid epidemic. It is associated with increased risk of several chronic diseases. Bariatric surgery is an effective and safe technique for the treatment of morbid obesity and co-morbidities related to obesity. Objective: This study aimed to evaluate the effect of lifestyle modification module on patients’ compliance postoperative bariatric surgery. Method: A quasi experimental design was utilized for the study. A purposive sample of 104 patients with postoperative bariatric surgery who are selected according to certain inclusion criteria. Results: There was significant improvement in patients’ compliance post implementation of lifestyle modification module where the pre compliance mean score was 21.04±8.07 and the post mean score was 33.59±8.34. Conclusions: Lifestyle modification module has positive effect on improving patients’ compliance postoperative bariatric surgery. This demonstrates that the module is an effective intervention for postoperative counseling to improve bariatric surgery outcomes.